The relationship between satisfaction with life, dietary attitude, and comfort level in hemodialysis patients: Analysis with machine learning approach - Ciftci, Necmettin; Yildiz, Metin; Yildirim, Zeynep (Wiley, 2024)
IntroductionHemodialysis (HD) patients have become a serious public health problem, the number of which is increasing every year worldwide. This study aimed to determine the relationship between satisfaction with life, dietary attitude, and comfort level in patients receiving HD treatment.MethodsThis research was conducted in a relational cross-sectional descriptive design. The research was conducted with 174 patients (85% of the population) receiving HD treatment between March 20 and September 30, 2023. In the study, hierarchical regression analysis was performed with SPSS 25.0. Machine learning analysis and prediction were performed using R programming language, version 4.1.3.ResultsThe model used to determine the factors affecting satisfaction with life was significant and usable (F(2,171) = 25.855, p = 0.001). Attitudes of HD patients toward dietary therapy and their HD comfort levels together explained 22.3% of the total variance of satisfaction with life. In the regression model, according to the results of the t-test regarding the significance of the regression coefficient, the increase in the HD comfort levels of the participants (t = 2.668, p = 0.008) and the increase in the attitude of the HD patients toward dietary therapy (t = 5.897, p = 0.001) caused a statistical increase in satisfaction with life. According to Shapley values, the most important variable in the prediction of satisfaction with life variable is attitude for the dietary attitude.ConclusionIt was determined that the increase in the comfort levels of HD patients and their positive dietary attitudes increased satisfaction with life. It is recommended to provide education to increase patients' diet attitudes and comfort levels.
Keywords: comfort; dietary attitude; hemodialysis; satisfaction with life